2017
DOI: 10.1136/thoraxjnl-2016-209919
|View full text |Cite
|
Sign up to set email alerts
|

Functional phenotypes determined by fluctuation-based clustering of lung function measurements in healthy and asthmatic cohort participants

Abstract: Our method identified dynamic functional asthma and healthy phenotypes, partly independent of atopy and inflammation but related to genetic markers on the locus. The method can be used for disease phenotyping and possibly endotyping. It may identify participants with specific functional abnormalities, potentially needing a different therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…However, a 20‐year follow‐up rate of 54% in population‐based studies can be considered as acceptable and we showed that the followed‐up participants did not strongly differ from the nonparticipants in regard to the main clinical characteristics, and in particular across the cluster‐based asthma phenotypes, limiting the risk for selection bias in our study. The applied clustering method relied on characteristics measured at a single point in time, therefore does not account for the short‐term fluctuations of the parameters that might contain information for asthma phenotyping, as recently shown for the lung function parameters . The analysis relies on multiple testing, possibly leading to inflation of the false discovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, a 20‐year follow‐up rate of 54% in population‐based studies can be considered as acceptable and we showed that the followed‐up participants did not strongly differ from the nonparticipants in regard to the main clinical characteristics, and in particular across the cluster‐based asthma phenotypes, limiting the risk for selection bias in our study. The applied clustering method relied on characteristics measured at a single point in time, therefore does not account for the short‐term fluctuations of the parameters that might contain information for asthma phenotyping, as recently shown for the lung function parameters . The analysis relies on multiple testing, possibly leading to inflation of the false discovery rate.…”
Section: Discussionmentioning
confidence: 99%
“…SA cohorts have now been followed up in different locations worldwide, with the aim of improving our understanding of asthma and in particular of severe asthma. The more recent cohorts include the ProAR [3] Cohort from Salvador in Brazil and the European U-BIOPRED Cohort (Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes) [6], which were preceded by others such as ENFUMOSA [7] (The European Network for Understanding Mechanisms of Severe Asthma), BIOAIR [8], The Severe Asthma Research Programme (SARP) in the United States of America [9], The Severe Asthma Cohort of WESSEX, in the United Kingdom [10], and The Cohort for Reality and Evolution of adult Asthma in Korea [11] (COREA) to name but a few. Bringing them together to determine similarities and differences in symptoms, lung function and inflammatory patterns may enable validation of previous findings from bio-clinical phenotyping of individual cohorts and may also indicate differences that will inform our understanding of risk factors, mechanisms of disease, treatments, environment and ultimately leading to improvements in management.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the FBC method includes a data-driven process for determining the tolerable amount of missing measurements (see supplementary material). This data-driven process has been described in detail elsewhere [9]. Briefly, a highly compliant subset of patients (i.e.…”
Section: Computational and Statistical Methodsmentioning
confidence: 99%
“…In this study we applied a recently developed method of fluctuation-based clustering (FBC) [9] to a prospective observational cohort consisting of children with mild to severe asthma. We hypothesized that applying an observer-independent and data-driven asthma phenotyping methodology solely based on fluctuations of daily PEF might help identify clusters that correspond to clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%